ANALISIS PENERAPAN ETIKA PADA BISNIS JASA AKOMODASI SEBAGAI SUATU STRATEGI MEMPERTAHANKAN PELANGGAN (KASUS PADA SURYA HOTEL DURI) - Setiadi, Fachri; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The study was conducted at Surya Hotel Duri. This study aims to determine the application of ethics conducted by Surya Hotel Duri, in the form of application of the principle of autonomy, the application of the principle of honesty, the application of principles of equity, mutual benefit application, and the application of moral integrity. The number of those 100 people. The data obtained through the questionnaire and then further processed using descriptive statistics. The result is the application of ethics that do Surya Hotel Duri are quite good and reasonably fit.Keywords: analysis, application of ethics, Surya Hotel Duri